(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
This article tackled a rigorous review of plant anatomy and its history. The anatomy of the plant is significantly essential, and it is grown all over the world. However, most of it is produced in tropical and subtropical countries, and just a few of its species are grown in temperate zones. The anatomical studies are preliminary studies that come before the critical studies of these plants and fulfill the necessary learning for those studies. Although only a small number of plant taxa have really been explored physically up to this point, more species have likely been investigated chemically. This article provides a comprehensive look at the history of plant anatomy tools as well as anatomical investigations that have been conducted on plants